A communicative approach to community development: the effect of neighborhood storytelling network on civic participation. Issue 1 (1st January 2016) - Nah, Seungahn; Namkoong, Kang; Chen, Nien-Tsu Nancy; Hustedde, Ronald J.
Abstract: This study draws upon communication infrastructure theory to investigate how communication networks stimulate civic participation within a community development context. According to the communication infrastructure theory (CIT), local communication resources enable citizens to engage in collective action for the common good. The CIT proposes neighborhood storytelling networks (NSNs) as core communication assets: interpersonal discussion, connection to community organizations, and connection to local media, including traditional mass media and the Internet. To examine the relationship between NSN and civic participation, data were collected from a probabilistic, representative sample through a mail survey in a southeastern state ( N = 1154) in the US. Analysis reveals that individual sociodemographic characteristics and community context factors predicted connections to the NSN in a distinct way and such connections yielded positive relationships with civic participation. These results carry important theoretical, practical, and policy-related implications.